Analisis NIM, LDR, NPL, dan BOPO dalam Mempengaruhi ROA pada PT. BRI - Kesuma, Rangga Patti; Hasbullah , Hasbullah; Alie, Maria Septijantini; Surya, Andi; Yudhinanto, Yudhinanto; Oktaria, Eka Travilta; Bakti, Umar (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The study aims to analyze the influence of NIM, LDR, NPL, and BOPO on ROA at PT. Bank Rakyat Indonesia Tbk for the period 2016-2023. Research methodology: this study uses a quantitative method. The data analysis technique used in this study is multiple linear regression using the IBM SPSS version 25 program. The population in the study is quarterly financial reports, or in a year there are 4 (four) quarters (Q1, Q2, Q3, Q4), in the period 2016-2023. The sampling technique used in this study is saturated sampling, so that the number of samples is 32 samples according to the number of populations. Results: The results of this study show that increasing NIM will increase ROA in the company; LDR has a positive and significant effect on ROA, the results of this study show that increasing LDR will increase ROA in the Company; NPL has a negative and significant effect on ROA, the results of this study show that increasing NIM will decrease ROA in the Company; BOPO has a negative and significant effect on ROA, the results of this study indicate that increasing BOPO will decrease ROA in the company. Conclusion: Simultaneously, NIM, LDR, NPL and BOPO have a positive and significant effect on ROA, the results of this study indicate that in an effort to increase ROA, the factors that must be considered are the influence of NIM, LDR, NPL and BOPO. Limitations: This study is limited to only examining ROA, NIM, LDR, NPL and BOPO, further research can examine more broadly related to variables and research objects with a larger Company scale. Contribution: This study contributes to PT. Bank BRI Tbk, in an effort to increase ROA, it must pay attention to the important role of the NIM, LDR, NPL and BOPO ratios. So that the Company's performance can have implications for increasing the Company's performance.